Frontal lobe epilepsy surgery in childhood and adolescence: Predictors of long-term seizure freedom, overall cognitive and adaptive functioning - Ramantani, Georgia; Reuner, Gitta; Schubert-Bast, Susanne (Neurosurgery, 2018)
BACKGROUND: Although frontal lobe resections account for one-third of intralobar resections in pediatric epilepsy surgery, there is a dearth of information regarding long-term seizure freedom, overall cognitive and adaptive functioning. OBJECTIVE: To identify outcome predictors and define the appropriate timing for surgery. METHODS: We retrospectively analyzed the data of 75 consecutive patients aged 10.0 ± 4.9 yr at surgery that had an 8.1 yr mean follow-up. RESULTS: Etiology comprised focal cortical dysplasia (FCD) in 71% and benign tumors in 16% cases. All patients but one had a magnetic resonance imaging-visible lesion. At last follow-up, 63% patients remained seizure-free and 37% had discontinued antiepileptic drugs. Presurgical predictors of seizure freedom were a shorter epilepsy duration, strictly regional epileptic discharges in electroencephalography (EEG), and an epileptogenic zone and/or lesion distant from eloquent cortex. Postsurgical predictors were the completeness of resection and the lack of early postoperative seizures or epileptic discharges in EEG. Higher presurgical overall cognitive and adaptive functioning was related to later epilepsy onset and to a sublobar epileptogenic zone and/or lesion. Following surgery, scores remained stable in the majority of patients. Postsurgical gains were determined by higher presurgical performance and tumors vs FCD. CONCLUSION: Our findings highlight the favorable long-term outcomes following frontal lobe epilepsy surgery in childhood and adolescence and underline the importance of early surgical intervention in selected candidates. Early postsurgical relapses and epileptic discharges in EEG constitute key markers of treatment failure and should prompt timely reevaluation. Postsurgical overall cognitive and adaptive functioning is stable in most patients, whereas those with benign tumors have higher chances of improvement.